SERVANT LEADERSHIP: AN OVERVIEW AND BIBLIOMETRIC ANALYSIS - Aditya, Aditya; Sopiah, Sopiah (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469), 2022)
So far, many theories or styles of leadership have been developed, proposing different leadership styles. One of the most interesting leadership styles and possibly becoming a trend in the future is servant leadership. The philosophical foundation of the servant leadership style has been around for several years, but it is still not called the Servant Leadership style. Being a leader should be providing services or prioritizing or take good care of his team. The main purpose of this article is to examine the servant leadership style, want to know how this style of Servant leadership has developed over the last ten years (2013-2022)?, To find suggested facts related to servant leadership activities through Bibliometrics assisted with tools VOSviewer software for citation analysis, Coupling Bibliographic, Country Co-Occurence and top authors. This journal reviews Servant Leadership with the metadata of 44 scientific journals on Scopus and Lens.org. Jawad Khan was found as the most author reviewing Servant Leadership, as many as three scientific article documents (Zada, M et al, 2022), (Chen, M et al, 2022), (Zada, S, et al, 2022), and the United States as the highest state reviews servant leadership.